Mechanism of humic acid adsorption as a flotation separation depressant on the complex silicates and hematite. (1st March 2021) - Tohry, A.; Dehghan, R.; Zarei, M.; Chelgani, S. Chehreh
Graphical abstract: Highlights: Hornblende floatability in the presence of DDA is higher than augite. The depression effect of HA on hematite is significant. HA adsorption on the hematite surface is much higher than silicates. HA affinity to interact with Polyvalent cations follows the order: Fe 3+ ≫ Ca 2+ > Mg 2+ . HA adsorbs onto hematite surface via hydrogen and chemical bonds. Abstract: Humic acid (HA), as an environmentally friendly depressant, absorbed significant attention for possible cleaner production within mineral separation by selective separation, especially for reverse flotation of iron oxides. However, a few systematic studies were addressed its effect on the iron ore reverse cationic flotation in the presence of complex silicates and its adsorption mechanism on the surface of these minerals. This work is going to fill this gap by exploring the depression mechanisms of HA through the reverse cationic flotation (separation of hematite from complex silicates; augite and hornblende). Wettability analyses, micro and batch flotation scale tests were employed for such a purpose. Adsorption test, turbidity measurement, zeta potential measurement, and Fourier Transform Infrared (FTIR) analyses were conducted to understand HA adsorption's mechanism on these minerals' surface. Results relieved that at the low concentration of HA (20 mg/L), adsorption on the examined minerals' surface occurred. Based on the micro-flotation test results, HA's depression impact has the following order: hematite ≫ augite > hornblende. The surface analysis results suggested that HA can interact with the Fe ions on the hematite surface by chemical and hydrogen bonding. The same mechanism was observed for HA adsorption on the considered silicates; however, the adsorption rate was lower, while lower polyvalent cations are available on these silicates' surface.